Evaluation of perception threshold and pain in patients with Parkinson’s disease using PainVision® - Kurihara, Kanako; Fujioka, Shinsuke; Mishima, Takayasu; Tsuboi, Yoshio (Frontiers in Neurology, 2023)
Introduction Pain is one of the most frequent non-motor symptoms occurring in patients with Parkinson’s disease (PD). Traditionally, the Visual Analog Pain Scale (VAS), Numerical Rating Scale (NRS), and Wong-Baker Faces Pain Rating Scale (FRS) have been used for clinical pain assessment, but these assessments are subjective at best. In contrast, PainVision® is a perceptual/pain analyzer that can quantitatively evaluate pain as “pain intensity” based on “current perception threshold” and “pain equivalent current.” We evaluated the current perception threshold in all PD patients and pain intensity in PD patients with pain using PainVision®. Methods We recruited 48 patients with PD (PwPD) with pain and 52 PwPD without pain. For patients with pain, we measured current perception threshold, pain equivalent current, and pain intensity using PainVision®, in addition to evaluation by VAS, NRS, and FRS. For patients without pain, only current perception threshold was measured. Results There was no correlation with either VAS or FRS, whereas only weak correlation was identified for NRS (γ = −0.376) with pain intensity. Current perception threshold was positively correlated with duration of the disease (γ = 0.347) and the Hoehn and Yahr stage (γ = 0.259). As a quantitative evaluation of pain, pain intensity by PainVision® does not correlate with conventional subjective pain assessments. Discussion This new quantitative evaluation method of pain may be suitable as an evaluation tool for future intervention research. Current perception threshold in PwPD was related to the duration and severity of the disease and may be involved in peripheral neuropathy associated with PD.